Analisis Kritis Terhadap Penggunaan Media Sosial Aksera Surabaya - Umam, Khotibul (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2024)
Works of art are born from emotional impulses based on the worldview and interests of society that are passed down through generations. Fine art is related to the expression of beauty, entertainment, communication, skills, and hygiene. Fine art is an inseparable part of people's lives with various types that fulfill each individual's artistic taste. However, the era of technology and globalization has had an impact on the shift in art and cultural values. This research tries to analyze, explore the facts to what images and opinions occur on Aksera Surabaya's social media accounts. This research uses a constructivism criticism approach. The constructivism paradigm has the view that social life is not a natural reality, but a reality formed from the results of construction. This research uses the framing analysis method to find out and analyze the communication style and branding on Aksera Surabaya's social media. The results showed that Aksera Surabaya's social media did not maximize the existing features, such as Instagram Live, Reels music, and tags in Instagram posts. Through constructive criticism, this research provides solutions for content improvement and strategies for using social media, so that Aksera Surabaya's fine arts activities are better known publicy.